2013
DOI: 10.3201/eid1903.121287
|View full text |Cite
|
Sign up to set email alerts
|

Multidrug-Resistant Tuberculosis, Somalia, 2010–2011

Abstract: In a nationwide survey in 2011, multidrug-resistant tuberculosis (MDR TB) was found in 5.2% and 40.8% of patients with new and previously treated TB, respectively. These levels of drug resistance are among the highest ever documented in Africa and the Middle East. This finding presents a serious challenge for TB control in Somalia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
33
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 5 publications
7
33
3
Order By: Relevance
“…On the other hand, a higher frequency (27.7%) of monoresistance to any one of the four first-line drugs was reported in another study conducted in the country [20]. INH monoresistance (6.3%) recorded by the present study was comparable to that reported by studies conducted in other African countries such as the Central African Republic [21] and Somalia [22], which reported 5.8 and 5.7% respectively. In an eastern Ethiopian study [11], 9.5% monoresistance to INH was recorded.…”
Section: Discussionsupporting
confidence: 63%
“…On the other hand, a higher frequency (27.7%) of monoresistance to any one of the four first-line drugs was reported in another study conducted in the country [20]. INH monoresistance (6.3%) recorded by the present study was comparable to that reported by studies conducted in other African countries such as the Central African Republic [21] and Somalia [22], which reported 5.8 and 5.7% respectively. In an eastern Ethiopian study [11], 9.5% monoresistance to INH was recorded.…”
Section: Discussionsupporting
confidence: 63%
“…The conflict and violence, particularly in the south-central region, have caused massive population movements, exacerbated recently by severe drought, floods, and famine. The rates of maternal mortality and death in children < 5 years of age are among the highest in the world, and communicable diseases are the most common causes of illness and death [8]. In addition to TB [6, 8], advanced malignancies [9] are a serious public health problem.…”
Section: Discussionmentioning
confidence: 99%
“…Resistance to anti-TB drugs is considered an emerging problem, although the prevalence of multidrug-resistant TB (i.e., resistance to rifampin and isoniazid, the 2 most powerful anti-TB drugs) is unknown [24]. Somalia has an estimated TB rate of 10 per 100,000 inhabitants and a minimum number of 1,000 cases per year, and multidrug resistance has been documented [6].…”
Section: Discussionmentioning
confidence: 99%
“…Estimates show that 56% these MDR-TB patients have been successfully treated in the Eastern Mediterranean Region, and despite better outcomes compared to other regions, this number is much lower than WHO's defined goal of 75% for 2015 [37] . Country-specific studies highlight the urgent need for addressing MDR-TB, specifically among patients who are re-treated with anti-TB drugs [38][39][40] . The situation is becoming especially critical in Saudi Arabia due to high influence of travelers and migrating laborers from TB endemic areas, and also in Somalia which reports the highest prevalence of MDR-TB in the region [41,42] .…”
Section: Bridging Populationsmentioning
confidence: 99%